Beyond Borders: The Struggle for Food Sovereignty in the Americas - Massicotte, Marie-Josée; Beaudoin, Claudia; Bernier- Villeneuve, Thomas; Brousseau, Jessica (Kasarinlan: Philippine Journal of Third World Studies; Vol 26 No 1-2 (2011): Food Sovereignty in Southeast Asia)
For decades now, small producers have identified and resisted major problems that underline the current model of industrial food production, distribution, and consumption. Indeed, family farmers and peasants have long understood the risks and felt the multiple impacts of the globalizing model of agro-industrial development, which is based on export-oriented and capital-intensive monocultures. This article first distinguishes food sovereignty from food security before presenting sociopolitical movements fighting for food sovereignty, both in the North and the South of the Americas, as a way to maintain or develop innovative and sustainable models of agriculture, with examples from Mexico, Brazil, and Québec, Canada.
Keywords: peasantry, rural social movements, food sovereignty, agriculture, globalization